"Weighing" Two Qualitative Methods: Self-report Interviews and Direct Observations of Participant Food Choices. Issue 4 (November 2014) - Stuckey, Heather L.; Kraschnewski, Jennifer L.; Miller-Day, Michelle; Palm, Kimberly; Larosa, Caroline; Sciamanna, Christopher
Two primary forms of qualitative data collection in the health and social sciences include self-report interviews and direct observations. This study compared these two methods in the context of weight management for people who had varying degrees of success with weight loss ( n = 20). We asked general habits of eating as well as barriers to weight loss and maintaining a healthy diet. Video-recorded observations (20 minutes) followed audio-recorded interviews (45 minutes). Data were organized into four primary sections: (1) confirmatory data, where the interviews and observations held similar information; (2) discrepancies between what was reported in the interview and what was observed in the home; (3) new information that was unique to the observation and was not mentioned during the interview; and (4) clarification of data collected in the interview and observation. In general, the observations contained more confirmatory data for participants who had been successful at weight control than those who had not. The majority of observational data were emergent, which led to the discovery of new data of which we were unaware prior to the observations.